Reflections about Judea Pearl and his Contributions - Horvitz, Eric (Special UAI Session: Recognizing Judea Pearl's Turing Award, 2012)
It’s an honor to have been invited to share reflections about Judea Pearl and his contributions. Being asked to talk about Judea in front of this home audience is an interesting request as most people here understand and appreciate Judea’s work—and many of you know him well personally. Judea has been the heart and soul of a revolution in the use of probabilistic representations in AI and in computer science more broadly. His intellectual contributions and clear writing have also provided other disciplines with insights and building blocks, with influences in econometrics, statistics, and the philosophy of science.